Multimedia Courseware for Slow Learners:A Preliminary Analysis - Abdollah, Norfarhana; Wan Ahmad, Wan Fatimah; P. Akhir, Emelia Akashah (2010)

(untitled)
Emergences of technology had enabled the development of various innovative teaching-learning tools in education. The enjoyment offered by multimedia can increase learner's motivation and participation thus allowing them to retain the learning process in longer period compared to using traditional classroom method. As slow learners are difficult to maintain their learning attentions for long time span, multimedia courseware is believe to assist them. This paper presents the findings from a preliminary analysis of slow learners conducted in special education schools. In this study, qualitative methodology using interview with special education teachers and class observations were conducted to understand the slow learner's teaching-learning situations as a whole. The key findings from the analysis are slow learner's learning interest and behavior while using computer and the potential that multimedia courseware can bring in motivating and increasing their interest in learning. Several guidelines for designing multimedia courseware for slow learners are proposed. Conceptual framework is also being illustrated in this paper as guide in conducting further research. All these preliminary findings will assist in designing multimedia courseware and will successfully facilitate the slow learners as well as special education teachers.